The cyclicality of consumption, wages and employment of the public sector in the euro area - Ana Lamo; Javier J. Pérez; Ludger Schuknecht (European Central Bank (ECB), 2007)
This study examines the business cycle behaviour of public consumption and its main components; the public wage bill (including compensation per employee and public employment) and intermediate consumption in the euro area aggregate, euro area countries and a group of selected non-euro area OECD countries (Denmark, Sweden, the UK, Japan and the US). It looks across a large number of variables and methods, using annual data from 1960 to 2005. It finds robust evidence supporting that public consumption, wages and employment co-move with the business cycle in a pro-cyclical manner with 1-2 year lags, notably for the euro area aggregate and euro area countries. The findings reflect mainly the correlation between cyclical developments (automatic stabilizers), but also point to the important role of pro-cyclical discretionary fiscal policies.
Keywords: E62; E63; H50; 330; filtering; Public consumption; public employment; public wages; stylized facts; thick modelling; Öffentlicher Konsum; Vergütungssystem im öffentlichen Dienst; Öffentlicher Dienst; EU-Staaten